PENERAPAN PELATIHAN PENANGANAN KEADAAN DARURAT BAGI KARYAWAN DI BANDAR UDARA INTERNASIONAL JAWA BARAT - Astri Sri Nengsih; Dhiani Dyahjatmayanti (Pusat Riset dan Inovasi Nasional, 2023)
In order to improve the quality of human resources in dealing with emergency conditions, it is necessary to implement an emergency training program for employees. There is a need for research on identifying problems related to emergency training programs for employees who work at airports in order to provide knowledge so that they are alert and responsive to emergencies that occur. So far, it has not set about solutions to overcome problems related to emergency training programs for employees at West Java International Airport. This research was conducted in West Java. This type of research is qualitative. This study uses interview and documentation methods as data collection techniques. The results of this study indicate that in dealing with emergencies in the entire area of West Java International Airport, emergency procedures have been made, including: emergency preparedness procedures, emergency response procedures, post-emergency recovery procedures and supported by instructions. work related to emergencies, which is the division of organizational responsibilities for the emergency response team.